Isolation of lactic acid bacteria from swine milk and characterization of potential probiotic strains with antagonistic effects against swine-associated gastrointestinal pathogens - Quilodrán Vega, Sandra Rayén (2016)
Probiotics are usually isolated from the gastrointestinal tract of humans and animals. The search of probiotics in human milk is a recent field of research, as the existence of the human milk microbiome was discovered only about a decade ago. To our knowledge, no reports regarding the potential probiotic effect of bacteria from swine milk were published. In this work, we isolated several lactic acid bacteria from swine milk and evaluated them for them potential as probiotics. Among the isolated strains, Lactobacillus curvatus TUCO-5E showed antagonistic effects against swine-associated gastrointestinal pathogens. TUCO-5E was able to reduce the growth of enterotoxigenic and enterohemorragic E. coli strains as well as pathogenic Salmonella. In vitro exclusion and displacement assays in intestinal epithelial cells showed a remarkable antagonistic effect for L. curvatus TUCO-5E against Salmonella TUCO-I7 and S. enterica ATCC 13096. Moreover, by using a mice model of Salmonella infection we were able to demonstrated that L. curvatus TUCO-5E preventive administration during 5 consecutive days was capable of decreasing the number of S. typhimurium in the liver and spleen of treated mice when compared to controls, and avoided dissemination of the pathogen to the blood stream. Then, we demonstrated here that swine milk is an interesting source for finding beneficial bacteria. In addition, the results of this work suggest that L. curvatus TUCO-5E is a good candidate for in vivo studying the protective effect of probiotics against intestinal infection and damage induced by Salmonella infection in the porcine host.